Idiopathic megabowel causing acute bowel obstruction: A case report. (May 2022) - Beji, Hazem; Najib, Fatma; Zaiem, Asma; Guelbi, Mohamed; Rebai, Wael; Kacem, Montassar
Abstract: Background: Idiopathic megabowel is a rare condition. Its physiopathology is still unclear. We report a case of a patient presenting with acute bowel obstruction due to idiopathic megacolon and megarectum that was successfully treated with proctocolectomy. Case presentation: A 65-year-old man, with a history of chronic constipation, presented to the emergency with acute bowel obstruction symptoms. His CT scan on admission showed a very dilated rectum and sigmoid colon filled with faeces. The patient was managed conservatively. Due to the deterioration of his condition. We opted for an emergency laparotomy and it revealed the important dilation of the descending colon, the sigmoid colon, and the rectum leading to a Hartmann procedure. degenerative lesions of the smooth muscle layers were seen on the histopthological report and the diagnosis of rectosigmoid idiopathic megacolon was made. Postoperatively, we performed a rectoscopy that showed a distended rectum full of faeces. We performed a proctectomy with colo-anal anastomosis. He had an uneventful recovery. Conclusion: Idiopathic megacolon is a rare condition. The pathogenesis is still unclear. Surgical treatment is the best option to prevent complications and to improve the quality of life of the patient. Highlights: Idiopathic megabowel is a rare condition. It is characterized by a persistent dilatation of the colon and the rectum. The physiopathology is still unclear. Acute bowel obstruction complicating idiopathic megabowel should be treated timely. Surgical treatment is the best option to prevent complications.